Advancing the framework for considering the effects of climate change on worker safety and health. Issue 11 (1st November 2016) - Schulte, P.A.; Bhattacharya, A.; Butler, C.R.; Chun, H.K.; Jacklitsch, B.; Jacobs, T.; Kiefer, M.; Lincoln, J.; Pendergrass, S.; Shire, J.; Watson, J.; Wagner, G.R.
ABSTRACT: In 2009, a preliminary framework for how climate change could affect worker safety and health was described. That framework was based on a literature search from 1988–2008 that supported seven categories of climate-related occupational hazards: (1) increased ambient temperature; (2) air pollution; (3) ultraviolet radiation exposure; (4) extreme weather; (5) vector-borne diseases and expanded habitats; (6) industrial transitions and emerging industries; and (7) changes in the built environment. This article reviews the published literature from 2008–2014 in each of the seven categories. Additionally, three new topics related to occupational safety and health are considered: mental health effects, economic burden, and potential worker safety and health impacts associated with the nascent field of climate intervention (geoengineering). Beyond updating the literature, this article also identifies key priorities for action to better characterize and understand how occupational safety and health may be associated with climate change events and ensure that worker health and safety issues are anticipated, recognized, evaluated, and mitigated. These key priorities include research, surveillance, risk assessment, risk management, and policy development. Strong evidence indicates that climate change will continue to present occupational safety and health hazards, and this framework may be a useful tool for preventing adverse effects to workers.